Tempo’s Watchdog Journalism toward the Indonesian Government’s Policy on COVID-19 - Muhammad Dicka Ma'arief Alyatalatthaf; Natalia Faradheta Putri (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
The second wave of COVID-19 hit Indonesia in July 2021. Tempo magazine published five editions about it throughout July-August 2021. This study aims to see how Tempo magazine frames its news about government policies in dealing with the second wave of COVID-19 in Indonesia. This research uses Robert M. Entman’s framing analysis model. The results showed that the government is inconsiderate and irresponsive to the current conditions of COVID-19. Accordingly, the government is inconsistent in implementing PPKM (lockdown). They are too focused on an economic recovery that they are planning on the COVID-19 therapeutic drugs and vaccination business, and there is a lack of coordination in the government body. Through its news framing, Tempo also carries out the function of watchdog journalism, which is implemented in three dimensions: the intensity of the scrutiny, the journalistic voice, and the source of the news event.